Why 25 Years? Notes on the Long Trajectory of Roger Barker's Research in Oskaloosa. Issue 1 (2nd January 2016) - Barker, Jonathan Shedd
ABSTRACT: Roger Barker pursued a research project on the behavior of people for 25 years. As Roger's son I observed it through several phases from child-under-study to academic researcher. The research was driven by a changing set of intellectual objectives. The first was to fill a gap in psychological research: to gather naturalistic descriptions of the behavior of children. When the research revealed that behavior settings were much more powerful predictors of behavior than were psychological variables, the intellectual goal changed to record the whole landscape of public behavior in the small town. The findings then required theoretical work to understand the forces that govern behavior settings. Roger's theory showed how smaller schools produced more participation and a greater sense of personal significance than did larger ones. The fourth phase was practical research, notably about the impact of school consolidation. The current interest in context raises the prospect that new thinking about the environment of human actions will benefit from the idea of behavior settings and the work of the Midwest Psychological Field Station.